2016
DOI: 10.1007/s10967-016-5079-8
|View full text |Cite
|
Sign up to set email alerts
|

Lichens and mosses as polonium and uranium biomonitors on Sobieszewo Island

Abstract: In the study the activities of polonium 210Po and uranium 234U, 238U radionuclides in moss and lichen samples were determined using the alpha spectrometry. Different lichens and mosses were collected around the Sobieszewo Island (northern Poland) and investigated for potential use as biomonitors for 210Po and 238U deposition. Mosses and lichens have a high efficiency in capturing 210Po and 238U from atmospheric fallout. The obtained results showed that 210Po, 238U concentrations are changing in analyzed thallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Plants and aquatic organisms have been reported to accumulate U from soils and water in the range of 0.08-3500 mg kg −1 (Huang et al, 1998;Dienemann et al, Frontiers in Environmental Science frontiersin.org Chang et al, 2005;Sakamoto et al, 2008;Viehweger and Geipel, 2010;Caldwell et al, 2012;Cordeiro et al, 2016;Boryło et al, 2017;Li C et al, 2019;Bergmann and Graca, 2020). Hyperaccumulation of U from contaminated sites has been reported for several plant species and aquatic organisms (Dienemann et al, 2002;Chang et al, 2005;Viehweger and Geipel, 2010;Caldwell et al, 2012;Li C et al, 2019;Bergmann and Graca, 2020).…”
Section: Biota Accumulationmentioning
confidence: 99%
“…Plants and aquatic organisms have been reported to accumulate U from soils and water in the range of 0.08-3500 mg kg −1 (Huang et al, 1998;Dienemann et al, Frontiers in Environmental Science frontiersin.org Chang et al, 2005;Sakamoto et al, 2008;Viehweger and Geipel, 2010;Caldwell et al, 2012;Cordeiro et al, 2016;Boryło et al, 2017;Li C et al, 2019;Bergmann and Graca, 2020). Hyperaccumulation of U from contaminated sites has been reported for several plant species and aquatic organisms (Dienemann et al, 2002;Chang et al, 2005;Viehweger and Geipel, 2010;Caldwell et al, 2012;Li C et al, 2019;Bergmann and Graca, 2020).…”
Section: Biota Accumulationmentioning
confidence: 99%
“…There are large gaps in the current knowledge of radioecological situation in these areas. Lichen and mosses were selected as sample matrices for this study due to their ability to accumulate and concentrate radionuclides from the surface air, enabling their use as biomonitors of contaminants (Tuominen and Jaakkola 1973 ; di Lella et al 2003 ; Borylo et al 2017 ; Galhardi et al 2017 ). Besides global and local radionuclide depositions, other factors affecting the accumulated radionuclide concentration in lichen are, e.g., lichen species, the specific sampling site, and climatic factors (Borylo et al 2017 ; Galhardi et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mosses are widely used as biomonitors of atmospheric deposition because they are broadly distributed (essentially found everywhere), relatively easy to sample, and have a high capacity to trap and accumulate atmospheric particles [1][2][3][4]. Moss biomonitoring has been widely used to assess the atmospheric deposition of nitrogen [5][6][7][8][9], trace elements [10][11][12][13], persistent organic pollutants [14][15][16][17], microplastics [18,19], and radionuclides [20][21][22]. Numerous studies have shown that radionuclides accumulate in mosses [23][24][25], making them effective biomonitors for detecting radionuclides that occur in trace atmospheric concentrations.…”
Section: Introductionmentioning
confidence: 99%